HUBUNGAN PENGETAHUAN IBU TENTANG STUNTING DENGAN PEMBERIAN ASI EKSKLUSIF DI KLINIK BIDAN PRAKTIK MANDIRI RESTI YULIANI JAKARTA TIMUR - Nadia Syaripah Hanum (2021)
Stunting is a growth problem in child caused by lack of nutritional intake for a long time due to inappropriate nutrition. Mother's knowledge is one of the most influential factors as a cause of children who experiencing stunting. Mothers who have good knowledge tend to take preventive measures so that their children do not suffer from stunting. Breastfeeding has a very significant effect on the incidence of stunting in children. This study was conducted to analyze the relationship between maternal knowledge about stunting and exclusive breastfeeding at the Resti Yuliani Independent Practice Midwife Clinic, East Jakarta. The research used observational analytic with a cross sectional approach. The sampling of the research used a total sampling of 88 respondents. Data was collected through paper and g-form questionnaires consisting of mother's knowledge about stunting, exclusive breastfeeding, mother's education, mother's age, mother's occupation, child's gender and child's nutritional status (PB/U). The results of the chi-square analysis test obtained a value of p = 0.035 (p <0.05), which means that there is a relationship between maternal knowledge about stunting and exclusive breastfeeding at the Independent Practice Midwife Clinic Resti Yuliani, East Jakarta. Suggestions for further researchers to conduct a research is to analyzing the relationship related to the characteristics of children and mothers with mother's knowledge about stunting and exclusive breastfeeding.